2022
DOI: 10.1080/02670836.2022.2043029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of milled glass fillers on mode-II fracture toughness of polymer composites

Abstract: This work focuses on investigating the effect of interface fibre orientation with milled glass fillers on mode-II fracture toughness of [0°7/θ°//θ°/0°7] glass/epoxy laminates. The result reveals that the loading of 5 wt-% milled glass fillers in the epoxy matrix enhanced the interlaminar fracture toughness. Significantly, the filler-loaded samples improved the fracture toughness by 232% (3.32 times) in 0°/0° and 184% (2.84 times) in ±45° interface fibre orientation compared to the baseline samples. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Kumar et al 29 discriminated the failure modes in laminated composites using AE amplitude, rise time, counts, energy, duration and peak frequency. Moreover, Mei et al 30 used AE energy for investigating the fracture toughness 31,32 and failure strength prediction in polymer 33 and ceramic matrix 34 composites. They concluded that the residual strength of composites was associated with fiber bundles buckling and delamination 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al 29 discriminated the failure modes in laminated composites using AE amplitude, rise time, counts, energy, duration and peak frequency. Moreover, Mei et al 30 used AE energy for investigating the fracture toughness 31,32 and failure strength prediction in polymer 33 and ceramic matrix 34 composites. They concluded that the residual strength of composites was associated with fiber bundles buckling and delamination 35 .…”
Section: Introductionmentioning
confidence: 99%